2016
DOI: 10.1371/journal.pone.0167893
|View full text |Cite
|
Sign up to set email alerts
|

Manure Preferences and Postemergence Learning of Two Filth Fly Parasitoids, Spalangia cameroni and Muscidifurax raptor (Hymenoptera: Pteromalidae)

Abstract: The efficiency of host-seeking behavior is crucial to the reproductive performance of female parasitoids. Initially, parasitoids may use chemical information garnered from the microhabitat in which they emerge to locate hosts. Spalangia cameroni and Muscidifurax raptor are commercially available parasitoids of filth flies. Postemergence exposure to a specific manure may provide a way to increase parasitism in specific microhabitats found at livestock facilities upon release. In this study, female parasitoids o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Insecticides that are to be used in IPM regimes should be compatible with natural enemies of the targeted pests . One of the most common groups of natural enemies of the housefly are parasitoids in the genera Muscidifurax and Spalangia (Hymenoptera: Pteromalidae), both are pupal ecto‐parasitoids that are commercially used in many parts of the world . If these parasitoids develop and feed on a PPF‐treated fly host, they are likely to consume PPF and may thus be affected as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insecticides that are to be used in IPM regimes should be compatible with natural enemies of the targeted pests . One of the most common groups of natural enemies of the housefly are parasitoids in the genera Muscidifurax and Spalangia (Hymenoptera: Pteromalidae), both are pupal ecto‐parasitoids that are commercially used in many parts of the world . If these parasitoids develop and feed on a PPF‐treated fly host, they are likely to consume PPF and may thus be affected as well.…”
Section: Introductionmentioning
confidence: 99%
“…16 One of the most common groups of natural enemies of the housefly are parasitoids in the genera Muscidifurax and Spalangia (Hymenoptera: Pteromalidae), both are pupal ecto-parasitoids that are commercially used in many parts of the world. 17 If these parasitoids develop and feed on a PPF-treated fly host, they are likely to consume PPF and may thus be affected as well. Data on the compatibility of PPF with housefly natural enemies come from a single study, in which this insecticide was found to be harmless to the parasitoid Spalangia endius Walker in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Biological parasites were released on the farm as part of protocols for controlling immature stages, aiming to establish sustainable reductions in fly populations [5][6][7]. Previous studies have indicated that S. cameroni and M. raptor successfully reproduced on both fly species, S. calcitrans and Musca domestica, in dairy farming [22][23][24]. Azevedo et al [20] have already evaluated the predation capacity of the predatory mites from the Macrochelidae family on fly eggs and neonates.…”
Section: Parasitoids and Predator Agents Releasementioning
confidence: 99%
“…These disparities may have been partially due to environmental factors and variables that affect host or parasitoid abundance and distribution , and/or biological characteristics of the parasitoid species used. Recent research suggests that parasitoids commonly used as biological control agents may have preferences for specific animal manures (Machtinger and Geden 2015), and that these preferences are not easily manipulated or influenced by post-emergencepost-emergence learning (Taylor et al 2016). Commercial colony quality, microhabitat preferences, and a lack of understanding of the timing and methods of release could have also influenced the success of releases (Patterson and Rutz 1986;Peterson et al 1983).…”
Section: Use Of Pupal Parasitoids In Augmentative Biological Control Programsmentioning
confidence: 99%